PENGARUH KONSELING KELOMPOK DENGAN TEKNIK SOSIODRAMA UNTUK MENINGKATKAN SIKAP HORMAT TERHADAP GURU - Ahmad Anas Hasibuan; Alfin Siregar (UIN Sumatera Utara Medan, 2024)
Based on the research results, it shows that there is an influence of group counseling using sociodrama techniques to increase respectful attitudes towards guidance and counseling teachers in secondary schools. From the experimental class pretest results, an average score of 26.00 was obtained, while the control class pretest score obtained an average score of 25.8. The average pretest score for the learning outcomes of both classes is relatively low, this is because in class learning they do not carry out group counseling. As we know group counseling can. apply basic thinking (learning by moving and doing, learning by talking and hearing, learning by observing and picturing, and learning by problem solving and reflecting). As well as using various learning techniques that aim to make learning more enjoyable.